PERANAN KESULTANAN MELAKA DALAM PENGEMBANGAN AJARAN AGAMA ISLAM DI RIAU DAN KEPULAUAN RIAU - Khairul Amin; Ridwan Melay; Kamaruddin Kamaruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Malacca Sultanate is one of the historic Sultanate as having the tradecenter as well as the assessment centers teachings of Islam in the archipelago. Theentry of the teachings of Islam in the Sultanate of Melaka has brought a change in beliefsystems, Social Life, Economics, and Politics in the life of the Malay community,especially for those areas under the control of Melaka including Riau and Riau Islands.The purpose of research is to describe the history of Islam in the Sultanate of Melaka, toknow clearly who are the sultans who once ruled the Malacca Sultanate, know andunderstand what kind of role Malacca Sultanate in the development of the teachings ofIslam in Riau and Riau Islands, the effect of the inclusion of religious teaching Islam onthe lives of the Malay community. The method used in this research is the method ofHistorical and methods Kualitatif.Hasil this study are known to the advent of IslamdiKesultanan Melaka because the roles of the traders from the Middle East regionsailed into Malacca Sultanate, from Melaka then Islam spread almost throughout thearchipelago including Riau region and Riau Islands which brings about changes inbelief systems, Social life, Economics, and Politics in public life Melayu Riau and RiauIslands. Based on the research results, it can be concluded Malacca Sultanate wasinstrumental in the development of Islamic teachings in the Riau Islands andRiau.Dimana with the advent of Islam in public life has brought a very significantchange in the lives of the Malay community, especially in terms of confidence, SocialLife, Economics, and Politik.Islam not only as a religious doctrine, but as the rules inlife that leads to the road more glorious.Keywords: Sultanate of Malacca, Islam, Riau and Riau Islands